متطلبات حوكمة الذكاء الاصطناعي في الجزائر – الواقع والمأمول- - لعريوي عبدالرزاق (جامعة الوادي University of Eloued, 2024)
ارتبط مفهوم الذكاء الاصطناعي بتعليم الآلة لتصبح قادرة على تقديم قدرات مشابهة للبشر في مختلف المجالات، وقد شكل أحد المحاور التي تسعى المؤسسات والدول لاستخدامه والاستفادة من مزاياه المتعددة لتجني منه وفورات اقتصادية ورفاه اجتماعي وأرباحاً مادية وتميز في سوق الأعمال وكفاءة إدارية في إدارة الشأن العام؛ غير ان استخدامه بغير وعي قد يجلب مخاطر إن لم يحوكم بالكيفية المثلى. تهدف هذه الورقة البحثية إلى توضيح متطلبات حوكمة الذكاء الاصطناعي، بالإضافة إلى أهمية تبنيه بالكيفية التي تسمح باستخدامه بالكيفية التي تضمن الاستفادة المثلى منه، والإشارة إلى واقع ومقومات حوكمته في الجزائر وافاقه المستقبلية، وذلك من خلال اتباع منظور تحليلي قائم على استقراء لواقع التجربة الجزائرية والممارسات والتجارب الجديرة بذلك، واستنباط الكيفيات التي تضمن حوكمة استخداماته. The concept of artificial intelligence is linked to machine learning to become capable of providing capabilities similar to humans in various fields, and it has formed one of the axes that institutions and countries seek to use and benefit from its multiple advantages to reap economic savings, social welfare, and profits, distinction in the business market, and administrative efficiency in managing public affairs; However, its unconscious use may bring risks if it is not governed in the best way. This research paper aims to clarify the requirements for governance of artificial intelligence, in addition to the importance of adopting it in a way that allows it to be used in a way that ensures optimal benefit from it, and to point out the reality and components of its governance in Algeria and its future prospects, by following an analytical perspective based on an extrapolation of the reality of the Algerian experience and practices and experiences worthy of that, and deducing the methods that ensure the governance of its uses.
Artificial Intelligence Governance Requirements in Algeria - Reality and Hopes -
Keywords: الذكاء الاصطناعي، الحوكمة، التعلم العميق.